Evaluation Of Dust Exposure To Truck Drivers Following The Lead Haul Truck - W. R. Reed; J. A. Organiscak (The National Institute for Occupational Safety and Health (NIOSH))
Haul trucks have the potential to generate large amounts of respirable dust. This respirable dust has been shown to be a health hazard to personnel, especially if it has a high silica content. Lack of dust sampling data from haul trucks prompted the completion of a study to quantify respirable dust concentrations. These field studies were conducted measuring instantaneous respirable dust at stationary locations from passing haul trucks at a stone quarry and at a coal mine site. Fugitive dust levels from haul trucks were analyzed to characterize dust dispersion. This analysis indicates safe following distances for haul trucks and other heavy equipment to avoid overexposure of respirable dust from the lead haul truck.